COMPARISON OF THERMAL INSULATION OF GLASS WOOL AND SUPERBTEX TO THE DRYING RATE OF FISH DRYING EQUIPMENT - Firdaus, Aneka; Gunawan, Gunawan; Saputra, M. A. Ade; Haryani, Nina (Politeknik Negeri Sriwijaya, Indonesia, 2023)
The use of glasswool or Superbtek insulation material in a fish dryer is one way to reduce the heat coming out of the fish dryer, so that the heat temperature utilized for the fish drying process will be maximized. These two insulation materials will be compared which one is better able to reduce heat. This fish dryer will be made with certain dimensions as needed, this tool design measures: 100 cm long, 50 cm wide, and 50 cm high for the outer wall, and 90 cm long, 40 cm wide, 40 cm high for the inner side wall. The height of the tool frame legs is 70 cm. Glasswool and Superbtex materials are affixed to the outside wall. The two insulation materials will be analyzed how much they affect the heat on the wall of the dryer, aiming to get the best insulation material between the two for the drying rate. With the experimental method, it was found that using Superbtex insulation material; the temperature inside the dryer was 94.200C and the temperature of the outer wall was 45.680C, the average drying rate was 4.306 gr/min, with the use of Glassswool insulation, the temperature of the inside wall of the dryer was 83.50C and the temperature of the outside wall of the dryer was 47.580C, the average drying rate was 3.489 gr/min. So superbtex insulation material is better to use than glasswool insulation material.